2022
DOI: 10.1101/2022.06.18.496602
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of genome-scale, base-resolution DNA methylation profiles across 580 animal species

Abstract: Methylation of cytosines is the prototypic epigenetic modification of the DNA. It has been implicated in various regulatory mechanisms throughout the animal kingdom and particularly in vertebrates. We mapped DNA methylation in 580 animal species (535 vertebrates, 45 invertebrates), resulting in 2443 genome-scale, base-resolution DNA methylation profiles of primary tissue samples from various organs. Reference-genome independent analysis of this comprehensive dataset quantified the association of DNA methylatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 134 publications
1
4
0
Order By: Relevance
“…The most comprehensive previous study of animal methylation assayed 580 species and matches the global patterns presented here 35 . However, this impressive catalog was created using RRBS and is subject to the typical challenges caused by bisulfite conversion, as well as enrichment for CpG dense regions and lack of accurate transposon identification due to short reads and loss of mapping ability.…”
Section: Discussionsupporting
confidence: 67%
“…The most comprehensive previous study of animal methylation assayed 580 species and matches the global patterns presented here 35 . However, this impressive catalog was created using RRBS and is subject to the typical challenges caused by bisulfite conversion, as well as enrichment for CpG dense regions and lack of accurate transposon identification due to short reads and loss of mapping ability.…”
Section: Discussionsupporting
confidence: 67%
“…Profiling samples collected following amputation revealed no significant changes in DNA methylation patterns, despite widespread transcriptomic and chromatin accessibility changes. [ 50 ] Thus, even during a physiological process that is characterized by dramatic changes in cell identity and behavior, the DNA methylation pattern remained unchanged. Another example provided by our studies of zebrafish mutants with DNA hypomethylation showed widespread gene expression changes, but none could be attributed to loss of promoter methylation.…”
Section: Dna Methylation: Pattern and Functionmentioning
confidence: 99%
“…In contrast, available evidence indicates that vertebrate genomes are predominantly heavily methylated ( Angeloni & Bogdanovic, 2021 ) and display cytosine DNA methylation at CpG dinucleotides, except for CpG sites from genomic regions with high CpG ratios and GC contents—regions also known as “CpG islands” (CGIs) ( Al Adhami et al, 2022 ). However, the paradigm of DNA methylation in invertebrates has been recently challenged as growing evidence shows that it is more sophisticated than previously assumed ( De Mendoza et al, 2019 ; Klughammer et al, 2022 ). A recent comparative analysis of DNA methylation profiles across 580 animal species (including 45 invertebrates) revealed that the total amount of 5mC in the genome of many invertebrates species is well within the levels seen in vertebrates ( Klughammer et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the paradigm of DNA methylation in invertebrates has been recently challenged as growing evidence shows that it is more sophisticated than previously assumed ( De Mendoza et al, 2019 ; Klughammer et al, 2022 ). A recent comparative analysis of DNA methylation profiles across 580 animal species (including 45 invertebrates) revealed that the total amount of 5mC in the genome of many invertebrates species is well within the levels seen in vertebrates ( Klughammer et al, 2022 ). The haplosclerid demosponge Amphimedon queenslandica (Hooper & Van Soest, 2006), for example, showed a hypermethylated genome, with methylation levels and patterns showing strong similarities with vertebrates ( De Mendoza et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation